Footwear and footstrike change loading patterns in running - Nordin, A. D.; Dufek, J. S. (Journal of Sports Sciences, 2020)
Loading rates have been linked to running injuries, revealing persistent impact features that change direction among three-dimensional axes in different footwear and footstrike patterns. Extracting peak loads from ground reaction forces, however, can neglect the time-varying loading patterns experienced by the runner in each footfall. Following footwear and footstrike manipulations during laboratory-based overground running, we examined three-dimensional loading rate-time features in each direction (X, Y, Z) using principal component analysis. Twenty participants (9 M, 11 F, age: 25.3 ± 3.6 y) were analysed during 14 running trials in each of two footwear (cushioned and minimalist) and three footstrike conditions (forefoot, midfoot, rearfoot). Two principal components (PC) captured the primary loading rate-time features (PC1: 42.5% and PC2: 22.8% explained variance) and revealed interaction among axes, footwear, and footstrike conditions (PC1: F (2.1, 40.1) = 5.6, p = 0.007, Eta 2 = 0.23; PC2: F (2.0, 38.4) = 62.3, p < 0.001, ?Eta2 = 0.77). Rearfoot running in cushioned footwear attenuated impact loads in the vertical direction, and forefoot running in minimalist footwear attenuated impact loads in the anterior-posterior and medial-lateral directions relative to forefoot running in cushioned shoes. Loading patterns depend on footwear and footstrike interactions, which require shoes that match the runner`s footstrike pattern.